Potential new clinical therapies for Chagas disease. Issue 3 (May 2014) - Bustamante, Juan M; Tarleton, Rick L
<x xml:space="preserve">Abstract</x> Chagas disease is the highest impact parasitic disease in the Americas but often goes untreated due to the shortcomings of currently available therapeutics. Thus there is an urgent need for new treatment options and growing interest in drug development for the infection. This review summarizes some of the recent advances and failures in this realm, with particular emphasis on recently published studies and unpublished results presented at a recent Chagas Drug Discovery Consortium meeting.